Dark spies - Dunn, Matthew, 1968- (Dunn, Matthew, 1968- Spycatcher novel., 2014)
On the run from the CIA, intelligence operative Will Cochrane heads to the U.S. to uncover a diabolical spymaster at the center of an international conspiracy.